Behavioral insights into insurance purchase among flash flood survivors in Malaysia - Mahalasmi Radhakrishnan; Mohammad Nurul Hassan Reza; Abdullah Al Mamun; Muhammad Mehedi Masud; Zafir Khan Mohamed Makhbul (Humanities & Social Sciences Communications)
Abstract A catastrophic flood is a notorious phenomenon with severe consequences for individuals and governments. Purchasing flood insurance can be a viable solution to mitigate the effects of such disasters. This study examines the factors that influence the purchase intention and behavior of flood insurance among people living in flash flood-prone areas. By integrating the protection motivation theory, a comprehensive model is proposed. Based on convenience sampling, data were collected from 331 Malaysians living in flash flood-prone areas in Klang Valley, Malaysia. Partial least squares—structural equation modeling was employed to analyze the data. This study reveals that flood awareness has a positive impact on perceived severity (β = 0.137, f 2  = 0.019) and vulnerability (β = 0.354, f 2  = 0.143). However, past flood experience does not have a significant effect on response efficacy and cost. Additionally, flood insurance purchase intention is influenced by perceived severity (β = 0.121, f 2  = 0.026), response efficacy (β = 0.487, f 2  = 0.391), response cost (β = −0.153, f 2  = 0.041), and functional value (β = 0.241, f 2  = 0.094) but not by perceived vulnerability. Moreover, functional value (β = 0.149, f 2  = 0.020) and purchase intention (β = 0.211, f 2  = 0.040) significantly influence purchase behavior. This study provides a unique perspective on decision-making dynamics in a flood-prone region and offers valuable insights for practitioners and policymakers to enhance the insurance industry by integrating the factors of flood awareness, past experience, and functional value with protection motivation theory. This study suggests that flood insurance company managers adjust their policy guidelines to better serve their stakeholders in similar contexts.